A combinatorially developed Zr-Ti-Fe-Al metallic glass with outstanding corrosion resistance for implantable medical devices. (15th March 2019) - Khan, Muhammad Mudasser; Shabib, Ishraq; Haider, Waseem
Abstract: This paper explores a Zr-Ti-Fe-Al metallic glass, fabricated via combinatorial approach using magnetron co-sputtering. The paradigm of combinatorial synthesis is demonstrated via X-Ray Diffraction and Transmission Electron Microscopy. The metallic glass is probed electrochemically in contrast with a distinguished biomaterial, commercially pure titanium (cp-Ti). The metallic glass shows no susceptibility to pitting corrosion and manifests better corrosion resistance properties than cp-Ti in terms of roughly one order improvement in corrosion current density and charge transfer resistance, attributed to the combined role of homogeneous amorphous structure and chemically stable oxide film predominantly composed of ZrO2 and TiO2 . Graphical abstract: Unlabelled Image